Biotechnology policy implementation from a systems perspective - Adham, Khairul Akmaliah; Kasimin, Hasmiah; Said, Mohd Fuaad (Faculty of Economics and Management, Universiti Putra Malaysia, 2011)
This study utilizes Viable System Model (VSM) in diagnosing one policy implementation call Malaysian Biotechnology policy. The policy implementation is viewed from the innovation theory, which regards research and development (R&D) as the core of innovation commercialization, which in turn become the nucleus for a firm’s growth. Subsequently, the growth of firms as a group can lead to an industry’s development. This study conducted interviews with the agencies involved in the policy implementation and took advantage of the extensive information relating to the agencies that are available in the public domain, by using content analysis as the study’s methodology. This study enhances the understanding on the full use of VSM; it provides policy makers and implementers a guide in improving existing systems or designing new ones, while researchers are afforded an applicable theoretical conceptualization from a systems thinking perspective.